2022
DOI: 10.1002/jssc.202101008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, hepatic disposition, and heart tissue distribution of 14 compounds in rat after oral administration of Qi‐Li‐Qiang‐Xin capsule via ultra‐high‐performance liquid chromatography coupled with triple quadrupole tandem mass spectrometry

Abstract: In the present study, a specific and sensitive approach using ultra-highperformance liquid chromatography coupled with triple quadrupole tandem mass spectrometry was developed and validated for the quantitative analysis of 14 constituents in rat plasma, liver, and heart. The method was fully validated and successfully applied to pharmacokinetic, hepatic disposition, and heart tissue distribution studies of 14 compounds after the oral administration of Qi-Li-Qiang-Xin capsule. Ginsenoside Rb1, alisol A, astraga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…astragaloside IV, ginsenoside Rb1, periplocymarin, benzoylmesaconine, benzoylhypaconine, and alisol A. 11 A second report that relied on the identification of compounds with bioactivity on isolated cardiomyocytes yielded astragaloside, tanshinone IIA, ginsenoside Re, songorin, calycosin-7-O-β-D-glucopyranoside, hesperidin and alisol A. 12 Similar listings of constituents (including other ginsenosides) have been published by others.…”
Section: Identification Of Active Ingredients Of Qiliqiangxinmentioning
confidence: 90%
See 1 more Smart Citation
“…astragaloside IV, ginsenoside Rb1, periplocymarin, benzoylmesaconine, benzoylhypaconine, and alisol A. 11 A second report that relied on the identification of compounds with bioactivity on isolated cardiomyocytes yielded astragaloside, tanshinone IIA, ginsenoside Re, songorin, calycosin-7-O-β-D-glucopyranoside, hesperidin and alisol A. 12 Similar listings of constituents (including other ginsenosides) have been published by others.…”
Section: Identification Of Active Ingredients Of Qiliqiangxinmentioning
confidence: 90%
“…orientale (Oriental waterplantian), (7) the rhizome of Polygonatum odoratum (Mill.) Druce (solomonseal), (8) the flower of Carthamus tinctorius (L.) (safflower), (9) the root bark of Periploca sepium Bunge (Chinese silkvine), (10) the pericarp of Citrus reticulata Blanco (dried tangerine peel), and (11) the branch of Cinnamomum cassia Perl (cassia twig). These ingredients are combined in capsules that are available for prescription.…”
Section: Formulation and Active Ingredients Of Qiliqiangxinmentioning
confidence: 99%
“…In recent years, the pharmacokinetics of sinapic acid ( 2 ) from SS in rat plasma has been investigated by a validated UPLC-MS/MS method ( Li et al, 2020 ). The dynamic distribution of sinapine thiocyanate ( 3 ) has been monitored using a validated UPLC-MS/MS method ( Tang et al, 2022 ). The quantitative method validation was established according to the United States Food and Drug Administration (FDA) guidelines ( US Food and Drug Administration, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the pharmacokinetic study is an effective method for predicting effective substances and explaining their effective mechanisms. It plays a crucial role in evaluating clinical efficacy, guiding the rational use of traditional Chinese medicines, and promoting their development [3,4]. It has been reported that pathological conditions may affect biomembrane permeability, transporters, and metabolic enzyme activities in vivo, thus causing changes in absorption, distribution, metabolism, and excretion processes [5,6].…”
Section: Introductionmentioning
confidence: 99%